Evaluation of washback effects of ESP end - term test for second-year students at UEB-VNUH on teachers at Faculty of English - ULIS - VNUH - Phạm, Thu Hà (ĐHNN, 2017)
Evaluation of washback effects of ESP end - term test for second-year students at UEB-VNUH on teachers at Faculty of English - ULIS - VNUH as the topic of her research. It is hoped that this study would make a modest contribition to better the teaching of Business English to second-year students at UEB - VNUH.